ANALYSIS OF CHANGES IN STATIC STRESS BEFORE THE 2019 AMBON EARTHQUAKE BASED ON COULOMB FAILURE STRESS AND B-VALUE - Kurniawan, Andri
On September 26, 2019, a large Mw 6.5 earthquake significantly impacted the cities of Central Maluku, Ambon and West Seram in eastern Indonesia. This earthquake broke an active fault that has not been mapped and exhibits source characteristics with a very complex rupture process. In this study, the combination of spatial distribution of Coulomb failure stress (?CFS) and b-value is used to determine the geodynamic processes that cause earthquakes and serve as an indicator of increased seismicity. All information on seismic events in the Maluku Region (2- 5°S Latitude and 127-132°E Longitude) from 1980 to 2021 at a depth of 40 km or less. The correlation between the modeling results ?CFS and the b-value shows that the source fault segment the 2019 Ambon earthquake was in a high stress state with a positive ?CFS of 0.1 bar (0.01 MPa) and a low b-value of 0.7 before earthquake occurs. The source segment of the earthquake was reactivated by stress changes from a series of large earthquakes around the Manipa and South Buru faults. The Kawa Shear Zone (KSZ) and Bobot-East Seram show stress changes on active faults followed by high seismicity. Distribution of positive stress on the receiver faults suggest that the Ambon City may experience higher seismicity in the future.